Upskilling-Upgrading Desa Wisata Sukoharjo-Bojonegoro melalui Program 3ED (Edu-Etno-Eco-Digital Tourism) - Nafi Atin Hasanah; Reni Dwi Setiawati; Mitha Saharani; Ratna Indriani; Muhamad Iqbal Fachri Zulfani; Ludfi Anggraeni; Febrika Dilla Saputri; Achmad Zidan Zulfa; Abdullah Gymnastiar; Sabila Nurfalah Ardiana; Nuzilatur Rohmah; Sekar Mahkota Trihapsari Cendana Wangi; Putri Nafisatul Aisyah; Fitara Aulia Triningtiyas; Wulan Kumala Sari; Chyntia Heru Woro Prastiwi (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACT The village of Sukoharjo in Kalitidu District, Bojonegoro Regency, has natural potential, including rice fields, fertile lands along the Bengawan Solo River, and an abundance of fruit crops such as crystal guava, water guava, avocado, longan, starfruit, and honey jackfruit. The village also has natural resources like oil wells and cultural heritage in the stories of Joko Popok and Mbok Rondo Mori. This potential, however, has not been fully utilized for developing a tourist village that could serve as an income generator for the local community. This community service program aims to implement the Sukoharjo-Bojonegoro Tourist Village Upskilling-Upgrading Program through the 3ED Program (Edu-Etno-Eco-Digital Tourism). “Upskilling” involves enhancing the skills of stakeholders and villagers in managing tourism potential, while “upgrading” focuses on improving the systems, procedures, and operations of the tourist village to be more efficient and effective. Upskilling and upgrading village tourism will create opportunities to stimulate the local economy, increase village income and welfare, expand employment opportunities, and contribute to poverty reduction. This program has produced five tourism packages, tested with kindergarten/RA and elementary/MI students: Edutourism 1, Edutourism 2, Ed-tourism 3, Ecotourism, and Ethnotourism. To strengthen the online marketing of these tourism packages, the community service team organized digital marketing training for village officials, women's tourism groups, and youth organizations.  ABSTRAKDesa Sukoharjo Kecamatan Kalitidu Kabupaten Bojonegoro memiliki potensi alam berupa lahan persawahan,  daerah subur tepian Sungai Bengawan Solo, dan hasil perkebunan buah jambu kristal, jambu air, alpukat, kelengkeng, belimbing, dan nangka madu. Desa ini juga memiliki kekayaan alam sumur minyak serta budaya cerita kisah Joko Popok dan Mbok Rondo Mori. Potensi ini belum digunakan sepenuhnya untuk pengembangan desa wisata yang dapat menjadi income generator bagi masyarakat setempat. Kegiatan PkM ini bertujuan mengadakan Program  Upskilling-Upgrading Desa Wisata Sukoharjo-Bojonegoro melalui Program 3ED (Edu-Etno-Eco-Digital Tourism). Upskilling terkait dengan peningkatan kemampuan stake holder dan masyarakat desa dalam mengelola potensi wisata, sementara upgrading memiliki makna peningkatan sistem, prosedur, dan cara kerja desa wisata agar menjadi lebih efisien dan efektif. Upskillling dan upgrading wisata desa akan membuka peluang untuk menggerakan ekonomi di tingkat lokal, meningkatkan pendapatan dan kesejahteraan masyarakat desa, memberikan kesempatan kerja yang semakin luas, dan berkontribusi mengurangi kemiskinan. Kegiatan pengabdian ini menghasilkan 5 paket wisata yang telah diuji cobakan kepada siswa TK/RA dan SD/MI, yaitu Edutourism 1, Edutourism 2, Edutourism 3, Ecotourism, dan Ethnotourism. Untuk memperkuat pemasaran online paket-paket wisata tersebut, tim PkM mengadakan pelatihan digital marketing bagi perangkat desa, ibu-ibu pokdarwis, dan pemuda Karang Taruna.